Application of the WHOQOL-BREF in a community segment as a subsidy for health promotion actions - Jacqueline Ramos de Andrade Antunes Gomes; Edgar Merchan Hamann; Maria Margarita Urdaneta Gutierrez (Revista Brasileira de Epidemiologia, 2014)
Introduction: This article presents the results of a research whose objective was to verify the prevalence of the perception reports regarding quality of life of library attendees in the public libraries in the Brazilian capital Federal District (FD) and the surrounding region and to analyse the factors related to dissatisfaction. Methods: An epidemiological transversal study was conducted in 592 individuals aged above 12 years old through the application of the WHOQOL-BREF/WHO questionnaire. Results: Higher frequencies of dissatisfaction were observed among women with ages above 25, with lower personal income and lower educational level. Dissatisfaction regarding the physical domain was more prevalent in the surrounding region than in the FD. Under the psychological domain, dissatisfaction predominated in people in the FD. Negative feelings, concentration difficulties and dissatisfaction regarding personal safety were referred by more than 25% of participants in both regions. Regarding the environment domain, lack of money and of leisure opportunities were the main complaints. In spite of these findings, interviewees referred being very satisfied with their health and quality of life. Conclusions: The results can be a sign that the quality of life in the study region is in alert level. A careful look at these data is needed to identify alternatives to change this situation, with effective actions for Health Promotion and development strategies for the study area. A planning and an intervention in the area of health education in public libraries is recommended, since these are very important social loci, that can be engaged in health promotion and disease prevention actions in the communities.